Aleutian Low variability for the last 7500 years and its relation to the Westerly Jet. (July 2022) - Nagashima, Kana; Addison, Jason; Irino, Tomohisa; Omori, Takayuki; Yoshimura, Kei; Harada, Naomi
Abstract: The Aleutian Low (AL) is one of the major atmospheric systems that determines environmental conditions during winter in the North Pacific Ocean, with impacts that affect the climates of both Asia and North America from mid- to high latitudes. However, the multi-centennial and longer scale behavior of the AL during the Holocene is not fully understood. In this study, AL variability since 7.5 ka was examined by applying the principal component analysis technique to published δ 18 O data derived from sedimentary calcite, peat, ice, and speleothem from western North America. The extracted Principal Component 1 (PC1) represents a dramatic change from the mid- to late Holocene, and appears to reflect long-term intensified AL related to interactions between orbitally-driven southward shift of the Westerly Jet (WJ) over East Asia and the northwestern Pacific, and intensification of the El Niño–Southern Oscillation. In contrast, PC2 is characterized by multi-centennial to millennial-scale oscillations, with a spatial loading pattern that suggests PC2 reflects AL intensity and position shifts. These oscillations are contemporaneous with both WJ latitude and/or the meandering path shifts over East Asia and solar activity change, suggesting that a decrease/increase in solar irradiance is related to AL variability via interactions with the WJ.